Correlated Functional Oxides : Nanocomposites and Heterostructures - Nishikawa, Hiroaki; Iwata, Nobuyuki; Endo, Tamio; Takamura, Yayoi; Lee, Gun-Hwan; Mele, Paolo (Springer International Publishing : Imprint: Springer, 2017)
This book introduces a variety of basic sciences and applications of the nanocomposites and heterostructures of functional oxides. The presence of a high density of interfaces and the differences in their natures are described by the authors. Both nanocomposites and heterostructures are detailed in depth by researchers from each of the research areas in order to compare their similarities and differences. A new interfacial material of heterostructure of strongly correlated electron systems is introduced.- Resumé vydavatel